Mother-child conversations about gender : understanding the acquisition of essentialist beliefs - Gelman, Susan A. (Monographs of the Society for Research in Child Development ;, 2004)
This looks at how mothers and young children talk about gender, to discover the potential role of language in fostering gender stereotypes. Mothers and their sons/ daughters, who were 2-1/2, 4-1/2, or 6-1/2 years of age, were videotaped discussing a picture book that focused on gender